Characterization of nanoscaled films on flat and grating substrates as some elements of plasmonics - Dmitruk, N.L.; Mayeva, O.I.; Korovin, A.V.; Mamykin, S.V.; Sosnova, M.V.; Yastrubchak, O.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The optical properties of multilayer structures consisting of dielectric, conductivity-oxide and nanoscaled metal layers, deposited on the planar substrates (witness samples) and surface relief ones (diffraction gratings) with micro- and nanoscale sizes, are investigated by AFM, spectral ellipsometry (SE), and photometric techniques. The SE-measured parameters are related to actual characteristics of the layers when specified the model of their near-surface regions. Using a parametrization of the layer dielectric function versus the wavelength and a fitting procedure, the dielectric parameters are determined. It is shown that the optical constants are affected by both the substrate morphology and the adjacent medium. Preliminary data about the influence of isolated particle plasmon excitations in 2D-substrates with the top nanoscaled Au layer on its optical properties are presented.